Efficacy and Safety of Fingolimod in Daily Practice: Experience of an Academic MS French Center - Roux, Thomas; Maillart, Elisabeth; Vidal, Jean-Sébastien; Tezenas du Montcel, Sophie; Lubetzki, Catherine; Papeix, Caroline (Frontiers in Neurology, 2017)
Introduction. Fingolimod is a sphingosin 1-phosphate receptor modulator. Fingolimod decreases the annual relapse rate in relapsing-remitting multiple sclerosis. The aim of this study was to assess the efficacy and safety of Fingolimod in daily practice in patients with relapsing-remitting multiple sclerosis, previously treated with Natalizumab or not, and systematically followed during at least 1 year. Methods. Data were collected from the patient files. Primary endpoint was the comparison between the annual relapse rate the year before Fingolimod onset and after 1 and 2 years of Fingolimod treatment. The secondary endpoints were the difference between EDSS at Fingolimod onset and after one and two years of treatment, and safety. Results. In the whole sample, we confirmed Fingolimod efficacy on the annual relapse rate (0.895 before vs. 0.364 one year after, p<.0001). Between our two groups (with or without Natalizumab before Fingolimod), the annual relapse rate was higher in the Natalizumab group during the first year but similar during the second year. The EDSS was stable during the first year of Fingolimod but significantly higher after two years (3.33 vs. 3.72, p=0.02). Concerning safety, only three patients had to discontinue Fingolimod because of tolerance issues. Conclusion. Our study showed that Fingolimod is safe in relapsing-remitting multiple sclerosis and can be used either after first-line treatments or after Natalizumab. However we observed a mild disability progression after 2 years.